(untitled) (Research, Society and Development, 2021)
Objective: To understand the experiences of mothers of children using cochlear implants as to the path to health care and schooling for their children. Methodology: Qualitative study, which used the cultural-historical theoretical framework of Vygotski, through the narrative of life and the unit of analysis of the experience. It was carried out in 2018, with four mothers of children who were cochlear implant users in phonoaudiological follow-up in the clinic of the Alagoas State University of Health Sciences, in the city of Maceió, Alagoas. Results: The experiences of the mothers showed the mobilization and persistence that each one needed to get the cochlear implant in their children, as well as the damage to the children’s development resulting from the late performance of the procedure and the difficulties in the health sphere and in school inclusion. Final considerations: From their experiences it was possible to understand the aspects that enhanced and/or weakened the children’s development, such as the unpreparedness of health professionals in passing on information about cochlear implantation to families during the first months of the children’s lives. The difficulties in the schooling process were also addressed, which involved the inexperience of educators and the absence of strategies aimed at the literacy practices of these children. It reinforced the need to create support networks for mothers and their children with cochlear implants, providing them with shelter to face difficulties throughout life and their inclusion in society.